COLONIZING AND RESETTLEMENT DEFORMATION OF THE NORTH CAUCASUS REGION IN THE PROCESS OF ITS ADAPTATION TO THE IMPERIAL MICROSOCIETY - Daria Korobeynikova (Гуманитарные и юридические исследования)
The article describes the ethnic and demographic situation in the North-Caucasus region, which took place before and during the Russian Empire penetration. The size of the local North-Caucasus population constantly fluctuated throughout the whole period of presentation of the Russian Empire in the North-Caucasus region. It is connected with many facts, including a series of epidemics, which reduced the number of mountaineers. The attempts of Russian authorities to oppose the spread of cholera epidemics in the region failed. On the other hand, some evident transformation took place in the North Caucasus under the Russian influence, namely the increase of the Slavonic population and resettlement of highlanders from their traditional areas to new lands. Originally new ethnic resettlement groups entailed no significant negative consequences for mountain societies, since the new settlers chiefly developed flat and steppe areas of the region. The difficulties of the migration deprived them of the power and means to expanse widely. The imperial authorities also hoped to transform mountain peoples socially and in cultural fields, so that it could provide an opportunity to localize the conflict of interests between the parties.